The effect of teamwork features by the innovative sessions and also the effective ways of communication between the software development and software consultant teams. - Peyyeti, Venkata (2012)
For the past few decades there were literature based on the teamwork quality and its six features. However, the effect for the teamwork quality by the innovative sessions conducted in the organization is not clearly explained. The main focus of this research is to explore the way the teamwork quality is disturbed by having the innovative sessions. For this the main focus was given to two specific teams, the software development team and software consultant team. And this study also mentions the communication feature between the two development and consultant teams. For this study a qualitative research was conducted and face-to-face and electronic interviews were done. The effective way of communication can be measured by considering the frequency and also the ways of communication. A total of six members were considered for the research, where three participants are from the software development team and three are from the software consultant team. The research clearly explain about the negative impact on the teamwork quality by the innovative sessions and also gives information related to the effective ways of communication between the software development team and the software consultant teams.